2008
DOI: 10.1111/j.1365-2958.2008.06463.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution of the pgdA gene to the virulence of Streptococcus suis

Abstract: SummaryStreptococcus suis is a major swine pathogen and emerging zoonotic agent. In this study we have determined the muropeptide composition of S. suis peptidoglycan (PG) and found, among other modifications, N-deacetylated compounds. Comparison with an isogenic mutant showed that the product of the pgdA gene is responsible for this specific modification which occurred in very low amounts. Low level of PG N-deacetylation correlated with absence of significant lysozyme resistance when wild-type S. suis was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 45 publications
7
80
1
Order By: Relevance
“…We showed that lysozyme triggers the production of EF1843 and that, in turn, this protein deacetylates GlcNAc residues in peptidoglycan. This mechanism, which allows E. faecalis to sense one of the components of the host innate immune response, is reminiscent of that described for Streptococcus suis (18). In S. suis, peptidoglycan de-N-acetylation is extremely low when the cells are grown in rich medium.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We showed that lysozyme triggers the production of EF1843 and that, in turn, this protein deacetylates GlcNAc residues in peptidoglycan. This mechanism, which allows E. faecalis to sense one of the components of the host innate immune response, is reminiscent of that described for Streptococcus suis (18). In S. suis, peptidoglycan de-N-acetylation is extremely low when the cells are grown in rich medium.…”
Section: Discussionmentioning
confidence: 81%
“…In S. suis, peptidoglycan de-N-acetylation is extremely low when the cells are grown in rich medium. Although the host signal(s) inducing peptidoglycan de-N-acetylation has not been identified, the expression of S. suis deacetylase is strongly stimulated in vivo (18).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial aconitases are subject to oxidation and Fe/S cluster loss, but the apo-form can still play regulatory roles (16,18). PgdA has been shown to be upregulated in response to oxidative stress and upon contact with neutrophils (10,28). Failure of the acnB strain to upregulate PgdA expression under 12% O 2 conditions is in contrast to the wild type, and it led us to hypothesize aconitase was playing a role in deacetylase regulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S5A in the supplemental material). We next reasoned that the major bactericidal factor could be macrophages, neutrophils, or serum, since all have been previously implicated in the killing of lysozyme-sensitive bacteria (9,50,51). Upon the infection of bone marrow-derived macrophages, only a small defect was observed when the pgdA oatA pbpX triple mutant, the most lysozyme-sensitive strain, was used (see Fig.…”
Section: Resultsmentioning
confidence: 99%